Development of Library Information System Web-based of SMA Negeri 1 Mojolaban Sukoharjo - Widyasari Nur Fadhilah; Maryam Maryam (Universitas Muhammadiyah Surakarta, 2021)
SMA Negeri 1 Mojolaban has a library with several librarians. The library system used by SMA Negeri 1 Mojolaban still uses conventional methods, which results in less optimal library services. Based on the obstacles experienced by SMA Negeri 1 Mojolaban, a library information system is needed that can make it easier for librarians to manage data. This study aims to assist librarians in managing library administration, reporting, and free letter libraries. This research was developed with the waterfall method which consists of several stages, namely System Requirements Gathering and Analysis, System Development, System Implementation and study coding, program testing, Deployment, and Maintenance. Program writing combines several languages such as HTML, Bootstrap, and the Codeigniter framework. After being developed, the system will be tested using a Blackbox and then Deployment using User Acceptance Testing (UAT). The system is considered valid and according to its function from the results of the Blackbox assessment. The UAT test results get an average value of 88.63% of the 52 participating respondents, so the system is good enough. The result is that it is easier for librarians to manage library data and book loan transactions.